Intergenerational similarities in the transition to marriage in Mexico - Julieta Pérez Amador (Revista Latinoamericana de Población, 2012)
This work builds on the idea that the transition to marriage is influenced simultaneously by social context, family context, and individual’s early biography and socioeconomic status. Unlike previous studies that examine the transition to marriage in Mexico, I consider theoretically and analyze empirically the role of intergenerational influences on marriage timing. Using data from the National Family Planning Survey, I estimated a set of nested discrete-time hazard models to evaluate the effects of mothers’ marriage age on children’s transition to marriage. I find that children of mothers who married young enter into marriage earlier than children of mothers who delayed marriage. This relationship persists after controlling for important socioeconomic factors. In fact, the effect of mothers’ age at marriage on children’s age at marriage is larger than the effect of mother’s education. I also find this relationship to be similar for both sons and daughters, suggesting that family influences are a key aspect of the transition to marriage in Mexico.